อิทธิพลของสภาวะลื่นไหลต่อการพร่องในการควบคุมตน โดยมีความต้องการทางปัญญาเป็นตัวแปรกำกับ - ปรางค์ทิพย์ พงษ์ประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
In the previous studies, passive activities like resting or inducing positive mood can prevent ego depletion, a state in which we use up our self-control resource. Active activities, like playing games, to induce a flow state may also be able to recuperate us from the fatigue. The purpose of this study was to examine activities that could ameliorate the effect of ego depletion. Upon a completion of a thought-suppression task, 134 participants were randomly assigned to one of the four intervening tasks: a) resting for about 6 minutes as control condition; b) flow state inducing task, where participants played a moderate level video game; c) non-flow state inducing task, where participants played the same game at a hard level; or d) enjoyment task, where participants watched a funny video clip. After that, they were presented with difficult Thai proverbs anagram puzzles. The scores and the amount of time they spent on the puzzles indicated the amount of their willpower. Results showed that the levels of need for cognition (NFC) significantly influenced the anagram performance scores (F(1,126) = 20.33, p < 0.001), but there was no difference in the scores among the four conditions. Nonetheless, there was a significant interaction between the four conditions and NFC on the time spent on the anagram (F(3,126) = 2.77, p < 0.05). Results also showed a significant main effect of NFC on the time spent on the anagram (F(3,126) = 5.67, p < 0.05). These results failed to support that a flow state facilitates participant’s performance on the anagram task. Nonetheless, the results showed that the anagram performance following the thought suppression task depended on the level of participants’ NFC.